Implementation of Quality Assurance and Accreditation Policy in Open Distance Learning Teacher Education Programs in Pakistan - Muhammad Ajmal (JCTE, 2023)
The study aimed to explore the existing practices in the implementation of accreditation and quality assurance measures of teacher education programs running through open distance learning in Pakistan and to probe dichotomy or policy disconnects in proposed implementation of an external accreditation and quality assurance system for teacher education program through distance education institutions.